Asian monsoon and vegetation shift: evidence from the Siwalik succession of India. (28th August 2022) - Bhatia, Harshita; Srivastava, Gaurav; Adhikari, Purushottam; Tao, Su; Utescher, Torsten; Paudayal, Khum N.; Mehrotra, Rakesh C.
Abstract: Quantitative Miocene climate and vegetation data from the Siwalik succession of western Nepal indicate that the development of the Indian summer monsoon has had an impact, though in part, on vegetation changes. The climate and vegetation of the Lower (middle Miocene) and Middle (late Miocene–Pliocene) Siwalik successions of Darjeeling, eastern Himalaya, have been quantified. Reconstructed climate data, using the Coexistence Approach, suggest a decrease in winter temperatures and precipitation during the wettest months (MPwet) from the Lower to Middle Siwalik. The floristic assemblage suggests that Lower Siwalik forests were dominated by wet evergreen taxa, whereas deciduous ones became more dominant during the Middle Siwalik. The vegetation shift in the eastern Himalayan Siwalik was most likely due to a decrease in MPwet. The quantified climate–vegetation data from the eastern and western Himalayan Siwalik indicate that changes in the Indian summer monsoon had a profound impact on vegetation development during the period of deposition. We suggest that the decrease in winter temperature and summer monsoon rainfall during the Middle Siwalik might be linked with the Northern Hemisphere glaciation/cooling or a number of other things that were also going on at the time, including the continued rise of the Himalaya, and drying across the Tibetan region, which may have affected atmospheric circulation regionally.